Kajian Kenyamanan Lingkungan Ruang Komputer Terhadap Pemenuhan Syarat Suhu Udara, Pencahayaan, Dan Akustik Dengan Metode Deskriptif Kualitatif - Fasikhi Fasikhi; Uras Siahaan; Margaretha Maria Sudarwani (Industrial Engineering, Engineering of Faculty, Universitas Kadiri, 2023)
The Comfort against the influence of air temperature, humidity, indoor lighting, circulation and acoustics is part of the effort to improve the quality of the function of the room. If the room is comfortable, the activities that take place in it are optimal. This research is a qualitative descriptive method. The results in this study were obtained that the average temperature and humidity in South Tangerang City exceeded the comfort threshold of 22.8-25.8 oC, the emission value per square meter was 349.9 Lux, the noise level of the research object from the average measurement results. is 57 dB. It was concluded that the Lux number is very close to ideal, so it is stated that the room lighting in the research object meets the requirements, while the noise level requires a noise damper or barrier to be able to reduce noise so that the room is comfortable to use.Comfort against the influence of air temperature, humidity, indoor lighting, circulation and acoustics is part of the effort to improve the quality of the function of the room. If the room is comfortable, the activities that take place in it are optimal. This research is a qualitative descriptive method. The results in this study were obtained that the average temperature and humidity in South Tangerang City exceeded the comfort threshold of 22.8-25.8 oC, the emission value per square meter was 349.9 Lux, the noise level of the research object from the average measurement results. is 57 dB. It was concluded that the Lux number is very close to ideal, so it is stated that the room lighting in the research object meets the requirements, while the noise level requires a noise damper or barrier to be able to reduce noise so that the room is comfortable to use.